The Rotterdam Radial Access Research: Ultrasound-Based Radial Artery Evaluation for Diagnostic and Therapeutic Coronary Procedures. (February 2016) - Costa, Francesco; van Leeuwen, Maarten A.H.; Daemen, Joost; Diletti, Roberto; Kauer, Floris; van Geuns, Robert-Jan; Ligthart, Jurgen; Witberg, Karen; Zijlstra, Felix; Valgimigli, Marco; Van Mieghem, Nicolas M.
Abstract : Background—: Radial artery wall might be damaged after cannulation for cardiac catheterization. We investigated structural changes of the radial artery wall after catheterization to understand whether these might predict radial pulsation loss or occlusion and local pain or functional impairment of the upper extremity. Methods and Results—: Ninety patients underwent transradial coronary angiography or intervention and were scanned with a high-resolution 40-MHz ultrasound before cannulation and at 3 hours and 30 days after procedure. Acute injuries of the radial artery occurred in all patients: dissection and intramural hematoma were the most common. However, these phenomena did not predict loss of radial pulsation or occlusion, local pain, or functional impairment at 30 days. Overall, the radial artery lumen was significantly reduced distal to the puncture site. Radial artery intima and total wall thickness increased 3 hours after puncture and persisted at 30 days. Radial occlusion and pulsation loss were observed in 3.9% and 9.2% of patients, respectively, at 30 days. Smaller radial artery lumen at baseline increased the risk of radial pulsation loss at 30 days (odds ratio, 1.23; P =0.049). The number of radial puncture attempts predicted pulsation loss (odds ratio, 2.64; P =0.027), occlusion (odds ratio, 3.49; P =0.022), and symptoms (odds ratio, 2.24; P =0.05) at 30-day follow-up. Conclusions—: After catheterization, radial artery puncture site is associated with increased intima and total wall thickness and with modest decrease of inner lumen diameter. Acute injuries of the vessel wall were ubiquitous, but contrary to repeated puncture attempts, did not seem to affect postprocedural radial occlusion or loss of pulsation. Abstract : Supplemental Digital Content is available in the text.